Investigating the relationship between digital technologies, supply chain collaboration and supply chain resilience in the context of COVID-19 - LIU, DAZHOU (2022)
The company faced increased uncertainty due to the global Covid-19 pandemic, shortages of raw material supplies from suppliers and changes in customer demand for certain products in the market. In such circumstances, it is difficult for companies to obtain and process information in an effective and timely manner, increasing their supply chain risk and supply chain disruption. Digital technology can help provide companies with information processing capabilities that can effectively collect, analyse and analyse data to improve the resilience of their supply chains in times of crisis. This study aims to investigate the impact of digital technology on supply chain resilience based on information processing theory and information sharing theory in the context of Covid-19 and a survey of Chinese manufacturers. The study takes into account both the moderating impact of trust and the mediating impact of supply chain collaboration. The findings demonstrate that the application of digital technologies improves supply chain resilience. The influence of digital technology on supply chain resilience is mitigated through supply chain collaboration. Trust moderates the impact of digital technology on supply chain collaboration but not on supply chain resilience. These studies have contributed to our understanding of the impact of digital technology on resilience and have informed companies' efforts to improve supply chain resilience in the context of the Covid-19 pandemic.